A DAF‐16/FoxO3a‐dependent longevity signal is initiated by antioxidants. (30th September 2013) - Kim, Juewon; Ishihara, Naoko; Lee, Tae Ryong
Abstract The precise mechanisms of antioxidant‐mediated longevity are poorly understood. We show that an antioxidant treatment can extend the lifespan of Caenorhabditis elegans (C. elegans) through the nuclear translocation of the forkhead box O transcription factor (FoxO) homolog DAF‐16. This pathway was found to involve 3‐phosphoinositide‐dependent kinase‐1 (PDK‐1) and serum‐ and glucocorticoid‐regulated kinase‐1 (SGK‐1), distinct from the known oxidative stress‐mediated mechanism in which FoxO3a translocation is regulated by c‐Jun N‐terminal kinase (JNK) and mammalian sterile 20‐like kinase‐1 (MST‐1). The differences in the mechanisms of FoxO activation by antioxidants and oxidants result in differences in FoxO phosphorylation and target gene expression. Based on these results, we found that a combination of early antioxidant treatment and late oxidant treatment is most effective for lifespan extension in C. elegans. © 2013 BioFactors, 40(2):247–257, 2014